Numerical Method - Wolfgang Boehm (Universities Press, 2003)
The development and analysis of constructive algorithms in Numerical Mathematics has become a focus of applied mathematics since the practical realization of these algorithms by electronic computers is no longer restricted to trivial examples. This book describes algorithmic solutions whose basic ideas are common to a variety of mathematical problems. By means of the methods presented, the reader will acquire the skills besides a fundamental knowledge to successfully work on related subjects in this field.